Clinical application of automated virtual orbital reconstruction for orbital fracture management with patient-specific implants: A prospective comparative study. Issue 9 (September 2022) - Chepurnyi, Yurii; Zhukovtseva, Olena; Kopchak, Andriy; Kanura, Oleksandr
Abstract: The aim of the study was to compare automated and manually conducted (slice-by-slice) virtual orbital wall reconstruction in terms of PSI design, manufacture, and clinical application for orbital fracture management. Patients with orbital wall fractures were evaluated for the potential for treatment with PSI, based on automated virtual wall reconstruction; these formed the main group. The surgical outcomes of these main-group patients' treatments were compared with those of the control group, which comprised patients randomly selected for this study, each of whom had the same orbital trauma patterns and were also managed with PSI. However, the control group patients were treated using 'slice-by-slice' virtual orbital reconstruction. Mean volume differences between the intact and reconstructed orbit were 0.65 ± 0.26 cm 3 in the main group (n = 23) and 0.57 ± 0.23 cm 3 in the control (n = 27; p = 0.837). In both groups, no cases of implant malposition or enophthalmos were detected after surgery. Orbital shape difference was similar for the main group and the control, at −3.3 ± 3.5% and 3.25 ± 2.5%, respectively ( p = 0.929). Diplopia was diagnosed at the 3-month follow-up in 13.0% of the main group and in 11.1% of the control ( p = 0.651). The average times spent on computer-aided design (CAD) procedures, including segmentation, virtual orbital reconstruction, and PSI design, were 36.7 ± 6.9 min in the main group and 72.9 ± 7.7 min in the control group ( p < 0.001). Within the limitations of the study it seems that PSI based on automated virtual reconstruction is a relevant alternative treatment option for orbital fractures because of its clinical efficacy that is similar to PSI based on a 'slice-by-slice' CAD protocol.